PKAPUSM BRINGS CHEER, GIFTS TO VISUALLY IMPAIRED STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BUKIT MERTAJAM, July 2015 Universiti Sains Malaysia (USM) is always committed to serve and contribute to the local community, and to provide the necessary support to help those in need. President of the USM Association of Academic & Administrative Staff (PKAPUSM) Associate Professor Dr P. Sundramoorthy said this at the iftar dinner hosted by PKAPUSM specially for the visually impaired children at Sekolah Kebangsaan Pendidikan Khas (SKPK) Alma (Penglihatan), here, recently.